Global Islamic Liberation Theology in the Local Context of Transgendered Indonesian Muslims - Hary Widyantoro (IAIN Ponorogo, 2019)
Abstract: The place of Lesbian, gay, bisexual, and transgender (LGBT) Muslims within Islamic normativity has become attention for scholars and activists, such as Kecia Ali and Scot Kugle, Nur Kholis who rethink the place of LGBT people in social, political, and religious lives. The paper discusses how Islamic liberation theology, as a global concept within the Muslim world, has inspired Nahdlatul Ulama Islamic University scholar-activists to hold discussions about the place of waria in Islam, at the Pesantren Waria Al-Fatah, Yogyakarta. However, as globalization leads to glocalization, the way the concept is understood and implemented differs from that global one. The study argues that global Islamic liberation theology influencing the activists in perceiving waria subject position has undergone “glocalization.” As Islamic liberation theology was used to fight against colonialism and capitalism, the scholar-activists now find in it the tools to fight against the oppression towards gender minorities, particularly waria. The study is based on interviews with several Nahdlatul Ulama activists, and participant observation in the Pesantren event.الملخص: أصبحت LGBT من المسلمين في الأعراف الإسلامية موضع اهتمام العلماء والناشطين مثل كيجيا علي وسكوت كوغل ونور خالص الذين قاموا بإعادة التفكير في مكانة فريق LGBT في الحياة الاجتماعية والسياسية والدينية. ناقش هذا المقال كيف أن لاهوت التحرير الإسلامي كمفهوم عالمي في العالم الإسلامي ألهم العلماء والناشطين في جامعة نهضة العلماء الإسلامية لعقد نقاش حول مكانة الخنثى في الإسلام في بسانترين